Pirates of the Caribbean : curse of the black pearl. - Depp, Johnny; Bloom, Orlando, 1977-; Rush, Geoffrey, 1951- (Disney, 2003)
A sweeping story set in an era when pirates scavenged the Caribbean seas. A young man, and a rogue pirate must battle a band of the world's most treacherous pirates in order to save a young woman who has been kidnapped, and recover a lost treasure.
Collector's edition.
Johnny Depp, Orlando Bloom, Geoffrey Rush.
Rated PG13.
DVD.